Análisis y determinación teórica de la rigidez de muros de mampostería reforzada en edificios de hasta dos niveles - Moya-Chavarría, Luis Fernando (Instituto Tecnológico de Costa Rica, 2011)
The project consists of the analysis and determination of the theoretical relative stiffness of reinforced masonry walls of buildings up to two levels to compare the results obtained manually and those obtained in the structural program SAP. The project aims to investigate the variables that will be used to further determine the reduction of rigidity of the walls structural program modeled on the SAP and compare with the theoretical values, when these conditions are varied, such as location and size in vain, whether doors, windows or both, thickness of blocks, and dimensions of the wall itself. Once you find out the specific rigidity is necessary to tabulate, to graph and have a global concept of models and their displacement by the effects of a load of 1000 kg was determined that the location of the span, and its size affects the rigidity of the wall and the wall also has a more rigid by increasing its thickness, and secondly for solid walls fixed formula approximate method reflects results very close to those obtained in the SAP and better still to multiply these results by factor of 0.73 the difference between them is less than 4%.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2011.
Keywords: Cargas; Geometría de Pared; MEF; Vanos; Agregados